An Analysis of the semantic relationships among tsukau, riyousuru, and shiyousuru in Japanese news media - Huzain, Nurimam Alfian; Imelda, Imelda; Taqdir, Taqdir (Universitas Dian Nuswantoro, 2025)
This research is conducted to find out the similarities and differences of the three verbs.This research discusses the semantic relationship between the verbs tsukau, riyousuru, shiyousuru in Japanese news media where the three verbs have similar meanings or the same meaning which is